Frailty and Caenorhabditis elegans as a Benchtop Animal Model for Screening Drugs Including Natural Herbs - Matsunami, Katsuyoshi (Frontiers in Nutrition, 2018)
Abstract Caenorhabditis elegans has been used in research for years to clarify the genetic cascades and molecular mechanisms of aging, longevity, and health span. Health span is closely related to frailty; however, frailty has a different concept and is evaluated using various parameters in humans, such as Fried’s Frailty Criteria. The C. elegans model has several advantages when performing a chemical screen to identify drug candidates. Several mouse models of frailty were recently developed, including a homozygous IL-10 knockout. These mouse models are useful for understanding human frailty; however, they are not appropriate for primary drug screening because they require large spaces, expensive cost, and time consuming assessments. Therefore a combination of these models may be a promising tool for discovering drugs and understanding the mechanisms of frailty. In addition, natural products and herbs are attractive sources of novel drugs with pharmacological activity and low toxicity, in fact, over 60% of currently-available drugs are estimated to be related to natural compounds. In this review, the possibility of identifying natural agents (i.e., herb extracts and compounds) that could improve frailty are proposed, and the advantages and limitations of these models are also discussed.